USING PROBIOTICS AND INULIN TO PROLONG FERMINTED DAIRY PRODUCTS SHELEF LIFE - & Thaer, Khaleel (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The fermented dairy products were prepared using, four different probiotic bacteria, Lactobacillus plantarum, Lb. rhamnosus, Lb. reutri and Lb. acidophilus individually. The fermented products were prepared using skimmed milk with the addition of 0, 1 and 2% inulin. The results showed that, the fat percentages were 0.14-0.18%, titrable acidity 0.69-0.89%, pH values 4.63- 4.84, total solids 11.95-13.85 and the protein percentages were 3.91-4.26% .The results showed that there were variation in the viable counts of probiotic bacteria according to the added percentage of inulin. It was found that the logarithmic viable counts for Lb. plantarum were 10.86, 12.41 and 13.91 when 0, 1 and 2% inulin was added respectively, while these counts were; 10.61, 12.30, 13.75, 9.97, 11.94, 13.75, 9.72, 10.10 and 11.20 cfu/g for Lb. rhamnosus, Lb. reutri and Lb. acidophilus, respectively. The decreased in logarithmic cycle was by 1.41-1.87 of viable counts (after 10 weeks at 5c) between the treatments of 0% inulin and those which is supported by probiotics addition. At the same conditions, the treatments with 1% inulin shawed 1.5 logarithmic cycle reduction in Lb. rhamnosus, Lb. reutri and Lb. acidophilus ,and 0.78 logarithmic cycle when Lb. planetarium were used. By using 2% inulin the logarithmic cycle decreased were one cycle for Lb. rhamrnosus, Lb. reutri and Lb. acidophilus while it was 0.33 cycle for Lb. planetarium at the same conditions.